Identification of variant α‐kafirin alleles associated with protein digestibility in grain sorghum. Issue 5 (7th July 2020) - Duressa, Dechassa; Bean, Scott; Amand, Paul St.; Tesso, Tesfaye
Abstract: Owing to its unique adaptation to challenging environments, sorghum [ Sorghum bicolor (L.) Moench] remains a vital food security crop for millions of smallholder communities in sub‐Saharan Africa. Elsewhere, the crop is used as an important feed ingredient. One key constraint undermining food and feed value of sorghum is reduced protein digestibility, which has been attributed to numerous causes. The aim of the present study was to investigate the impact of DNA sequence variations in genes coding for sorghum seed storage proteins (kafirins) on protein digestibility of sorghum grain. The entire kafirin gene family of 27 genes and six cysteine proteinase inhibitor genes were amplified from genetically diverse high‐ and low‐digestible sorghum genotypes in order to capture allelic variants that may be responsible for differences in digestibility. A pooled DNA library was prepared and deeply sequenced using the Ion Torrent DNA sequencing system. Variant alleles were called by mapping sequencing reads to the reference sorghum genome and tested for association with sorghum protein digestibility using quantitative (linear model regression) and qualitative (Chi‐square test) statistical analyses. Four α‐kafirin alleles, all located on chromosome 5, were strongly associated with protein digestibility. Three of the alleles were linked to high digestibility and one to low digestibility. These variants overlap with the genes, Sobic.005G185600, Sobic.005G188800, Sobic.005G189000 (high digestibility alleles), and Sobic.005G192801 (low digestibility allele). In silico predictive analysis showed the variants cause missense change in the amino acid sequences of the corresponding proteins. Molecular markers linked to these variant alleles may serve as breeding tools for genetic improvement of protein digestibility in sorghum.